Modern Fixed Prosthodontics: Digital Technologies, Materials, and Long-Term Clinical Outcomes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents a comprehensive analysis of the evolution of fixed prosthodontics in the context of modern digital dentistry, emphasizing the role of advanced technologies and novel restorative materials in improving precision, esthetics, and longevity. It explores the transition from traditional analog workflows to digital systems, including intraoral scanning, computer-aided design and manufacturing (CAD/CAM), and additive manufacturing techniques. The study discusses how these innovations have enhanced diagnostic accuracy, treatment efficiency, and patient outcomes. Furthermore, the article reviews contemporary restorative materials such as zirconia, lithium disilicate, and hybrid ceramics, examining their mechanical behavior, biocompatibility, and performance under clinical conditions. It also evaluates long-term clinical results, highlighting factors influencing success and failure in fixed prosthodontic rehabilitation. The purpose of this review is to integrate current knowledge and provide evidence-based recommendations for clinicians adopting digital workflows and advanced materials in restorative practice. This article provides a detailed exploration of how modern fixed prosthodontics has evolved through the integration of digital technology, advanced materials, and evidence-based clinical approaches. It focuses on the synergy between computer-aided design and manufacturing (CAD/CAM), intraoral scanning, additive manufacturing, and the development of new ceramic systems such as zirconia and lithium disilicate. The research emphasizes how these innovations have transformed the accuracy, efficiency, and predictability of restorative procedures. It also examines the influence of digital workflows on clinical outcomes, including marginal fit, esthetic performance, and long-term prosthesis survival. By analyzing material properties, digital precision, and biological responses, this paper aims to provide an in-depth understanding of how technological and material advances are shaping the future of fixed prosthodontics and improving patient-centered care.